Capital Budgeting Under Capital Rationing: An Analytical Overview of Optimization Models for Government - Khan, Aman (International journal of public administration, 2008)
Capital rationing is a real decision problem in government, yet it has never been seriously addressed in the literature on public budgeting. Conventional methods such as NPV or IRR that frequently appear in the discussion on the subject are limited in their scope. Alternative methods such as mathematical programming, which can substantially overcome some of the limitations of the conventional methods, have been extensively used in the private sector, but their applications have been few and far between in government. This article illustrates the potential these models hold for the capital rationing problem in government.